The Effect of Tax Avoidance on Liquidity, Profitability and Capital Structure PT. Bukalapak Tbk - Sri Widari (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study's overarching goal is to dissect the impact of tax evasion on the capital structure, liquidity, and profitability of PT. Bukalapak.com Tbk firms traded on the IDX from 2022 to 2024. This study used multiple regression analysis and a quantitative technique to find that capital structure, profitability, and liquidity impact tax evasion levels. There is a correlation between a company's liquidity and its propensity to participate in tax avoidance, and between a company's profitability and its propensity to use tax avoidance approaches to reduce cash outflows associated with tax payments. Because interest paid on debt is tax deductible, tax avoidance strategies are often accompanied with a capital structure that is heavily reliant on debt